Is Education Alone Enough to Sustain Improvements of Antimicrobial Stewardship in General Practice in Australia? Results of an Intervention Follow-Up Study - Robin Sangwan; Alicia J. Neels; Stella May Gwini; Sajal K. Saha; Eugene Athan (MDPI AG, 2023)
Sustained behaviour change and practice improvements for the optimal use of antimicrobials remains challenging in primary care. In 2018, a simple antimicrobial stewardship education programme involving guideline recommendations for common infections, antimicrobial audit reports, and local antibiograms resulted in significant improvements in guideline compliance and more appropriate antimicrobial prescribing by GPs. This observational follow-up study aims to examine the sustainability of the positive intervention effect after two years of implementation of the intervention. Practice-based data on all oral antimicrobial prescriptions issued by GPs were collected retrospectively to compare with intervention data and to measure the sustainability of the intervention effect. The data were analysed using a two-sample test of proportions. The primary outcomes included changes in the rate of prescription compliance with the Australian "Therapeutic Guidelines: Antibiotic" and the appropriateness of antimicrobial choice and duration of therapy. Overall, there was a significant decline in guideline compliance, from 58.5 to 36.5% (risk ratio (RR) (95% CI): 0.62 (0.52-0.74)), in the appropriateness of antimicrobial choice, from 92.8 to 72.8% (0.78 (0.73, 0.84)), and in the prescribed duration, from 87.7 to 53.3% (0.61 (0.54, 0.68)) in the intervention follow-up period. In respiratory infections and ear, nose, and throat infections, the rates of guideline compliance and appropriate choice and duration of antimicrobial prescription decreased significantly at p < 0.001. Appropriateness in the duration of antimicrobial therapy also significantly decreased for most antimicrobials. The evidence suggests that a simple and single-occasion antimicrobial stewardship education programme is probably not enough to sustain improvements in the optimal use of antimicrobials by GPs. Future research is needed to validate the results in multiple GP clinics and to examine the effect of sustained education programmes involving infection-specific and antimicrobial-targeted audits and feedback.